Development planning and policy: essays in honour of professor V.K.R.V. Rao - Gupta, B.D. (ed); Halan, Y.C. (ed.); Desai, P.B. (ed.) (New Delhi, 1982)
The present volume is offered by way of an humble tribute to the selfless contribution of Prof. V. K. R. V. Rao to the development of Indian economics in particular and social sciences in general in the course of his career that began in early 1930's. Some time back, a volume of essays was published in his honour at the initiative of the Institute of Economic Growth, one of the all-India institutions founded by him. The present set of essays is the result of a spontaneous endeavour of some of his students, associates and peers, most of whom had the privilege of knowing him and benefiting from his outstanding work and achievements in many fields.
Keywords: Economic Development